„My University” – Intensive Russian Language Training For Mobility Participation Starting From Elementary Level - Николова, Анета (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
This article purposes a learning model of Russian course in academic mobility programs. The training is focused on forming communication competencies for participating in exchange education and reading scientific research papers. The student’s native or first foreign language is a Slavic language and they are trained outside of the language environment. The course starts from elementary level, but it practically forms different level competencies/references (according to the Common European Framework of Reference for Languages) at the same time. The fast-paced preparation for the upcoming academic mobility (including majors-specific training) and the specific academic environment requires practical application of 1) developments in Linguopersonology and modelling the professional linguistic personality (LP), and 2) works on the problems of understanding and modelling the speech production process in contemporary Psycholinguistics. The proposed linguadidactic model relies on broadly used compensatory learning strategies and the positive interference of knowledge, including procedural knowledge, from the first language (mother tongue or foreign language).